Youth, Mosques and Islamic Activism: Islamic Source Books in University-Based Halaqah - Hilman Latief (Kultur, 2010)
This paper discusses the emergent religious enthusiasm among young Indonesian Muslims, with special reference to the university-based halaqah activists in Yogyakarta. Halaqah is a growing phenomenon of socio-religious expression amongst university students. Within the Islamic movement, it has had a new and powerful influence on Indonesian Muslim youth cultures. It provides a system within which young Muslims seeking a new personal or collective social identity can cultivate their religious orientation and thirst for knowledge. The regional spread of halaqah seems to correspond to the rapidly increasing number of publishers producing the halaqah reference materials that the movement desires, and making them readily available in the market. This paper aims to provide a comprehensive account of the religious, political, and cultural orientations of halaqah members by examining the reading materials circulating within halaqah. It argues that campus-based mosques are controlled by two kinds of halaqah, namely Salafi halaqah and Tarbiyah halaqah. The findings also show that Indonesia’s two mainstream moderate-traditionalist and reformist Islamic movements, Muhammadiyah and Nahdlatul Ulama, are less favored by university-based halaqah activists. This is partly because, although both these Indonesian mass organizations are faith-based civil society associations, they both overlook campus-based mosques in their main da‘wa agenda.